2015
DOI: 10.1016/j.micres.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of the acid trehalase encoded by the CgATH1 gene allows trehalose fermentation by Candida glabrata

Abstract: The emergent pathogen Candida glabrata differs from other yeasts because it assimilates only two sugars, glucose and the disaccharide trehalose. Since rapid identification tests are based on the ability of this yeast to rapidly hydrolyze trehalose, in this work a biochemical and molecular characterization of trehalose catabolism by this yeast was performed. Our results show that C. glabrata consumes and ferments trehalose, with parameters similar to those observed during glucose fermentation. The presence of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 86 publications
1
14
0
Order By: Relevance
“…We confirm the data of Zilli, Lopes [41], where it was shown that Ath1 is required for utilization of exogenous trehalose. Moreover, we show that Ath1 is present in the periplasm.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…We confirm the data of Zilli, Lopes [41], where it was shown that Ath1 is required for utilization of exogenous trehalose. Moreover, we show that Ath1 is present in the periplasm.…”
Section: Introductionsupporting
confidence: 92%
“…It requires divalent cations (Ca 2+ and Mn 2+ ) and has a pH optimum of 7 [34,35]. This neutral trehalase shows higher activity [39][40][41]. In S. cerevisiae, the acid trehalase enzyme is also present in the vacuole [37,38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another intriguing feature is how the Ima5 isomaltase reaches the extracellular/periplasmic space. The predicted IMA5 coding sequence does not encode an established signal sequence that would allow secretion of the enzyme, like is the case for invertase encoded by the SUC2 gene (Carlson et al 1983;Basso et al 2011), nor possible transmembrane segments that allow extracellular localization like for the acid trehalase in yeasts (Parrou et al 2005;Huang et al 2007;Zilli et al 2015). Nevertheless, there are examples of enzymes (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…This could have physiological justification. On the one hand C. glabrata is different from other yeasts in that it can only assimilate glucose and trehalose [62], [63]. This suggests that our S. cerevisiae model might not be a good estimator for trehalose turnover in C. glabrata.…”
Section: How Do Heat Shock Responses Of Other Fungal Species Conform mentioning
confidence: 91%